Cutting tool

By adopting multi-layer structural coating on cutting tools, the tool's wear resistance and defect resistance are improved by using alternating laminated structures of different compositions, the problem of short life of existing cutting tools is solved and longer tool life is achieved and higher performance stability.

CN119255879APending Publication Date: 2025-01-03SUMITOMO ELECTRIC HARDMETAL CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380042501.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-04-28
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The tool life of existing cutting tools is short in stainless steel turning processing, making it difficult to meet the needs of cost reduction and longevity.

Method used

A multi-layer structural coating is adopted which is alternately laminated by the first unit layer and the second unit layer. The first unit layer is composed of TiaAl1-a-bBbN, the second unit layer is composed of TicAl1-cN, and the third unit layer is composed of The fourth unit layer is alternately laminated with multi-layer structural coating, the third unit layer is composed of TidAl1-d-eBeN, and the fourth unit layer is composed of TifAl1-f-gBgN, and the peak intensity and semi-regulation are made by X-ray diffraction spectroscopy. Value width to improve hardness and toughness.

Benefits of technology

It significantly improves the wear resistance and defect resistance of cutting tools, extends the tool life, maintains stable hardness at high temperatures, inhibits cracking progress, and improves the overall performance of the tool.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119255879A_ABST
    Figure CN119255879A_ABST
Patent Text Reader

Abstract

A cutting tool provided with a base material and a coating film provided on the base material, the coating film including a first layer and a second layer provided closer to the base material than the first layer, the first layer comprising a multi-layer structure in which first unit layers and second unit layers are alternately laminated, the second layer comprising a plurality of first unit layers and a plurality of second unit layers being alternately laminated, and the first unit layers comprising a plurality of first unit layers and a plurality of second unit layers comprising a plurality of second unit layers. The average thickness of the first unit layer is from 2 nm to 50 nm (inclusive), the average thickness of the second unit layer is from 2 nm to 50 nm (inclusive), the first unit layer is composed of TiaAl1-a-bBbN (where 0.30 < = a < = 0.50 and 0 < b < = 0.10), the second unit layer is composed of TicAl1-cN (where 0.70 < = c < = 1.00), and in the first layer, the average thickness of the first unit layer is from 2 nm to 50 nm (inclusive), the average thickness of the second unit layer is from 2 nm to 50 nm (inclusive), and the average thickness of the second unit layer is from 2 nm to 50 nm (inclusive). The second layer is composed of a multilayer structure in which third unit layers and fourth unit layers are alternately laminated, the average thickness of the third unit layers is 2-100 nm (inclusive), the average thickness of the fourth unit layers is 2-100 nm (inclusive), and the ratio (T2 / T1) * 100 of the number of atoms (T2) of titanium to the total number of atoms (T1) of titanium and aluminum is 60% or more, and the second layer is composed of a multilayer structure in which the third unit layers and the fourth unit layers are alternately laminated, and the average thickness of the third unit layers is 2-100 nm (inclusive). The third unit layer is composed of TidAl1-d-eBeN, the fourth unit layer is composed of TifAl1-f-gBgN, and 0.25 < = dlt is satisfied; 0.45, 0 lt; e < = 0.10, 0.35 < = flt; 0.55, 0 lt; in the X-ray diffraction spectrum of the second layer, the ratio I (200) / I (002) of the peak intensity I (200) from the (200) plane to the peak intensity I (002) from the (002) plane, namely I (200) / I (002), is 2 or more, and the half-value width of the peak from the (002) plane is 2 or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to cutting tools. Background Art

[0002] Conventionally, in order to improve the performance of cutting tools, a coating film covering the surface of a substrate composed of cemented carbide, cubic boron nitride sintered body, or the like has been developed (for example, Patent Document 1).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: International Publication No. 2022 / 176057 Summary of the invention

[0006] The cutting tool disclosed herein comprises a substrate and a coating provided on the substrate, wherein:

[0007] The coating comprises a first layer and a second layer,

[0008] The second layer is disposed closer to the substrate than the first layer.

[0009] The first layer is composed of a multilayer structure in which first unit layers and second unit layers are alternately stacked.

[0010] The average thickness of the first unit layer is greater than or equal to 2 nm and less than or equal to 50 nm.

[0011] The average thickness of the second unit layer is greater than or equal to 2 nm and less than or equal to 50 nm.

[0012] The first unit layer is made of Ti a Al 1-a-b B b N constitutes,

[0013] in,

[0014] Satisfy 0.30≤a≤0.50,

[0015] 0<b≤0.10,

[0016] The second unit layer is made of Ti c Al 1-c N constitutes,

[0017] in,

[0018] Satisfying 0.70≤c≤1.00,

[0019] In the first layer, the percentage (T2 / T1)×100 of the number of titanium atoms T2 to the total number of titanium and aluminum atoms T1 is 60% or more,

[0020] The second layer is composed of a multilayer structure in which third unit layers and fourth unit layers are alternately stacked.

[0021] The average thickness of the third unit layer is greater than or equal to 2 nm and less than or equal to 100 nm.

[0022] The average thickness of the fourth unit layer is greater than or equal to 2 nm and less than or equal to 100 nm,

[0023] The third unit layer is composed of Ti d Al 1-d-e B e N constitutes,

[0024] The fourth unit layer is composed of Ti f Al 1-f-g B g N constitutes,

[0025] in,

[0026] Satisfy 0.25≤d<0.45,

[0027] 0 <e≤0.10、

[0028] 0.35≤f<0.55,

[0029] 0 <g≤0.10、

[0030] 0.05≤fd≤0.20,

[0031] In the X-ray diffraction spectrum of the second layer, the ratio I(200) / I(002) of the peak intensity I(200) from the (200) plane to the peak intensity I(002) from the (002) plane is greater than 2, and the half-value width of the peak from the (002) plane is greater than 2 degrees. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a schematic cross-sectional view showing an example of the structure of the cutting tool according to the first embodiment.

[0033] Figure 2 It is a schematic cross-sectional view showing an example of the structure of a film forming apparatus.

[0034] Figure 3 It is a schematic cross-sectional view showing an example of the structure of a film forming apparatus.

[0035] Figure 4 This is a diagram for explaining the measurement area when measuring the diameter of the maximum inscribed circle of the crystal grains of the first layer.

[0036] Figure 5It is a diagram for explaining a method of measuring the diameter of the maximum inscribed circle of the crystal grains of the first layer, and is a diagram schematically showing a bright field image of a measurement field.

[0037] Figure 6 It is a diagram for explaining the positional relationship between the crystal grains and the first unit layer and the second unit layer. DETAILED DESCRIPTION

[0038] [Problems to be Solved by the Present Disclosure]

[0039] In recent years, there has been an increasing demand for cost reduction, and a demand for longer tool life. For example, in stainless steel turning, there is a demand for cutting tools with a longer tool life.

[0040] Therefore, an object of the present disclosure is to provide a cutting tool having a longer tool life.

[0041] [Effects of the present disclosure]

[0042] The cutting tools of the present disclosure can have a longer tool life.

[0043] [Description of Embodiments of the Present Disclosure]

[0044] First, embodiments of the present disclosure will be described by way of examples.

[0045] (1) The cutting tool of the present disclosure comprises a substrate and a coating provided on the substrate, wherein:

[0046] The coating comprises a first layer and a second layer,

[0047] The second layer is disposed closer to the substrate than the first layer.

[0048] The first layer is composed of a multilayer structure in which first unit layers and second unit layers are alternately stacked.

[0049] The average thickness of the first unit layer is greater than or equal to 2 nm and less than or equal to 50 nm.

[0050] The average thickness of the second unit layer is greater than or equal to 2 nm and less than or equal to 50 nm.

[0051] The first unit layer is made of Ti a Al 1-a-b B b N constitutes,

[0052] in,

[0053] Satisfy 0.30≤a≤0.50,

[0054] 0<b≤0.10,

[0055] The second unit layer is made of Ti c Al 1-c N constitutes,

[0056] in,

[0057] Satisfying 0.70≤c≤1.00,

[0058] In the first layer, the percentage (T2 / T1)×100 of the number of titanium atoms T2 to the total number of titanium and aluminum atoms T1 is 60% or more,

[0059] The second layer is composed of a multilayer structure in which third unit layers and fourth unit layers are alternately stacked.

[0060] The average thickness of the third unit layer is greater than or equal to 2 nm and less than or equal to 100 nm.

[0061] The average thickness of the fourth unit layer is greater than or equal to 2 nm and less than or equal to 100 nm,

[0062] The third unit layer is composed of Ti d Al 1-d-e B e N constitutes,

[0063] The fourth unit layer is composed of Ti f Al 1-f-g B g N constitutes,

[0064] in,

[0065] Satisfy 0.25≤d<0.45,

[0066] 0 <e≤0.10、

[0067] 0.35≤f<0.55,

[0068] 0 <g≤0.10、

[0069] 0.05≤fd≤0.20,

[0070] In the X-ray diffraction spectrum of the second layer, the ratio I(200) / I(002) of the peak intensity I(200) from the (200) plane to the peak intensity I(002) from the (002) plane is greater than 2, and the half-value width of the peak from the (002) plane is greater than 2 degrees.

[0071] The cutting tools of the present disclosure can have a longer tool life.

[0072] (2) In the above (1), the nanoindentation hardness of the first layer at 25° C. may be 30 GPa or more. This improves the wear resistance of the cutting tool.

[0073] (3) Alternatively, in the above (1) or (2), the average thickness of the first layer is not less than 1.0 μm and not more than 20 μm. As a result, the number of stacked first unit layers and second unit layers in the first layer is large, and the effect of suppressing the progress of cracks is further improved. Therefore, large-scale damage to the coating can be suppressed, and the tool life of the cutting tool is prolonged.

[0074] (4) Alternatively, in any one of the above (1) to (3), the average thickness of the second layer is not less than 0.5 μm and not more than 10 μm. As a result, the number of stacked third and fourth unit layers in the second layer is large, and the effect of suppressing the progress of cracks is further improved. Therefore, large-scale damage to the coating can be suppressed, and the tool life of the cutting tool is prolonged.

[0075] [Details of the embodiments of the present disclosure]

[0076] Hereinafter, specific examples of the cutting tool disclosed in the present invention will be described with reference to the accompanying drawings. In the drawings disclosed in the present invention, the same reference numerals represent the same parts or equivalent parts. In addition, the dimensional relationships such as length, width, thickness, depth, etc. are appropriately changed for the clarity and simplification of the drawings, and do not necessarily represent the actual dimensional relationships.

[0077] In the present disclosure, expressions in the format of “A to B” refer to the upper and lower limits of a range (i.e., greater than A and less than B). When there is no unit recorded in A and only a unit is recorded in B, the unit of A is the same as that of B.

[0078] In the present disclosure, when a compound or the like is represented by a chemical formula, unless the atomic ratio is particularly limited, all conventionally known atomic ratios are included, and the atomic ratio is not necessarily limited to the atomic ratio within the stoichiometric range.

[0079] In the present disclosure, when more than one numerical value is recorded as the lower limit and the upper limit of the numerical range, a combination of any numerical value recorded in the lower limit and any numerical value recorded in the upper limit is also disclosed. For example, when more than a1, more than b1, and more than c1 are recorded as the lower limit, and less than a2, less than b2, and less than c2 are recorded as the upper limit, more than a1 and less than a2, more than a1 and less than b2, more than a1 and less than c2, more than b1 and less than a2, more than b1 and less than b2, more than b1 and less than c2, more than c1 and less than a2, more than c1 and less than b2, more than c1 and less than c2 are disclosed.

[0080] [Embodiment 1: Cutting Tool]

[0081] A cutting tool according to one embodiment of the present disclosure (hereinafter also referred to as “embodiment 1”) comprises a substrate and a coating provided on the substrate, wherein:

[0082] The coating comprises a first layer and a second layer.

[0083] The second layer is disposed closer to the substrate than the first layer,

[0084] The first layer is composed of a multilayer structure in which first unit layers and second unit layers are alternately stacked.

[0085] The average thickness of the first unit layer is greater than or equal to 2 nm and less than or equal to 50 nm.

[0086] The average thickness of the second unit layer is greater than or equal to 2 nm and less than or equal to 50 nm.

[0087] The first unit layer is composed of Ti a Al 1-a-b B b N constitutes,

[0088] in,

[0089] Satisfying 0.30≤a≤0.50,

[0090] 0<b≤0.10、

[0091] The second unit layer is composed of Ti c Al 1-c N constitutes,

[0092] in,

[0093] Satisfying 0.70≤c≤1.00,

[0094] In the first layer, the percentage (T2 / T1)×100 of the number of titanium atoms T2 to the total number of titanium and aluminum atoms T1 is 60% or more.

[0095] The second layer is composed of a multilayer structure in which third unit layers and fourth unit layers are alternately stacked.

[0096] The average thickness of the third unit layer is greater than or equal to 2 nm and less than or equal to 100 nm.

[0097] The average thickness of the fourth unit layer is greater than or equal to 2 nm and less than or equal to 100 nm.

[0098] The third unit layer is composed of Ti d Al 1-d-e B e N constitutes,

[0099] The fourth unit layer is composed of Ti f Al 1-f-g B g N constitutes,

[0100] in,

[0101] Satisfy 0.25≤d<0.45,

[0102] 0 <e≤0.10、

[0103] 0.35≤f<0.55,

[0104] 0 <g≤0.10、

[0105] 0.05≤fd≤0.20,

[0106] In the X-ray diffraction spectrum of the second layer, the ratio I(200) / I(002) of the peak intensity I(200) from the (200) plane to the peak intensity I(002) from the (002) plane is greater than 2, and the half-value width of the peak from the (002) plane is greater than 2 degrees.

[0107] The cutting tool of the present disclosure can have a long tool life. The reason is presumably as follows.

[0108] (i) The coating of the cutting tool disclosed in the present invention includes a first layer having a multilayer structure in which a first unit layer and a second unit layer are alternately stacked. The first unit layer and the second unit layer have different compositions. Therefore, near the interface between the first unit layer and the second unit layer, the progress of cracks generated from the surface of the coating during use of the cutting tool can be suppressed.

[0109] (ii) The first unit layer is composed of Ti a Al 1-a-b B b N (where 0.30≤a≤0.50, 0<b≤0.10) is satisfied. By adding a small amount of boron (B) to TiAlN, the hardness of the first unit layer is improved. The second unit layer is composed of Ti c Al 1-c N (wherein 0.70≤c≤1.00 is satisfied). The second unit layer has a high titanium (Ti) content and has excellent high temperature stability. In the present disclosure, the first layer is composed of a multilayer structure in which a first unit layer with high hardness and a second unit layer with excellent high temperature stability are alternately stacked, so that a stable hardness can be obtained even at high temperatures, and the resistance to crater wear is improved. Crater wear is wear mainly caused on the front cutting edge of the cutting tool due to the frictional heat between the cutting tool and the chips. Furthermore, the first layer is composed of a multilayer structure in which a first unit layer with high hardness and a second unit layer with lower hardness than the first unit layer are alternately stacked, so the defect resistance is also improved. Therefore, the crater wear resistance and defect resistance of the coating are improved in a balanced manner, and the tool life of the cutting tool is prolonged.

[0110] (iii) The Ti content and Al content of the first unit layer and the second unit layer are different. Therefore, the lattice of the first unit layer is different from that of the second unit layer, and lattice strain is generated in the first layer, so that the first layer can have high hardness. Therefore, the coating including the first layer can have excellent wear resistance.

[0111] (iv) In the first layer, the percentage (T2 / T1) of the number of titanium atoms T2 to the total number of titanium and aluminum atoms T1×100 is 60% or more. This allows the first layer to have excellent crater wear resistance, and the tool life of the cutting tool is prolonged.

[0112] (v) The coating of the cutting tool disclosed in the present invention includes a second layer composed of a multilayer structure in which a third unit layer and a fourth unit layer are alternately stacked. The third unit layer and the fourth unit layer have different compositions. Therefore, near the interface between the third unit layer and the fourth unit layer, the progress of cracks generated from the surface of the coating during use of the cutting tool can be suppressed.

[0113] (vi) The second layer has a higher aluminum (Al) content and higher toughness than the first layer. Therefore, the coating having the second layer can have excellent defect resistance.

[0114] (vii) The Ti content of the third unit layer is different from that of the fourth unit layer. Therefore, the crystal lattices of the third unit layer and the fourth unit layer are different, and the second layer is strained in the crystal lattice, so that the second layer can have high hardness. Therefore, the coating film including the second layer can have excellent wear resistance.

[0115] <Cutting tools>

[0116] The cutting tool of the first embodiment is not particularly limited in shape and purpose as long as it is a cutting tool. The cutting tool of the first embodiment can be, for example, a drill, an end mill, an indexable insert for milling, an indexable insert for turning, a metal saw, a gear cutting tool, a reamer, a tap, or a blade for grinding a crankshaft with a spike.

[0117] Figure 1 1 is a schematic partial cross-sectional view showing an example of the structure of the cutting tool of Embodiment 1. The cutting tool 100 includes a substrate 10 and a coating 20 provided on the substrate 10. The coating 20 includes a first layer 21 and a second layer 22. The second layer 22 is provided at a position closer to the substrate 10 than the first layer 21. The first layer 21 is composed of a multilayer structure in which a first unit layer 1 and a second unit layer 2 are alternately stacked. The second layer 22 is composed of a multilayer structure in which a third unit layer 3 and a fourth unit layer 4 are alternately stacked.

[0118] Substrate

[0119] The substrate 10 is not particularly limited. The substrate 10 may be made of, for example, cemented carbide, cermet, high-speed steel, ceramic, cubic boron nitride sintered body, diamond sintered body, etc. The substrate 10 is preferably made of cemented carbide because cemented carbide has excellent wear resistance.

[0120] Cemented carbide refers to a sintered body with WC (tungsten carbide) particles as the main component. Cemented carbide contains a hard phase and a binding phase. The hard phase contains WC particles. The binding phase binds the WC particles to each other. The binding phase contains, for example, Co (cobalt) and the like. The binding phase may also contain, for example, TiC (titanium carbide), TaC (tantalum carbide), NbC (niobium carbide), and the like.

[0121] Cemented carbide may contain impurities that are inevitably mixed in during its manufacturing process. Cemented carbide sometimes contains an abnormal layer called free carbon or "η layer" in its structure. Furthermore, cemented carbide may also be a cemented carbide that has been subjected to surface modification treatment. For example, cemented carbide may also contain a de-β layer on its surface.

[0122] The cemented carbide may contain 85 mass % or more and 98 mass % or less of WC particles, and 2 mass % or more and 15 mass % or less of Co. The average particle size of the WC particles may be 0.2 μm or more and 4 μm or less.

[0123] Co is softer than WC particles. As described later, if the surface of the substrate 10 is subjected to ion bombardment treatment, the soft Co can be removed. By making the cemented carbide have the above composition and making the WC particles have the above average particle size, appropriate concavities and convexities are formed on the surface after Co is removed. It is believed that by forming the coating 20 on the surface, an anchoring effect is exhibited, and the adhesion between the coating 20 and the substrate 10 is improved.

[0124] Here, the particle size of the WC particles represents the diameter of the circle circumscribed to the two-dimensional projection image of the WC particles. The particle size is measured using a scanning electron microscope (Scanning Electron Microscope; SEM) or a transmission electron microscope (Transmission Electron Microscope; TEM). That is, the cemented carbide is cut and its cut surface is observed with a SEM or TEM. In the observed image, the diameter of the circle circumscribed to the WC particles is regarded as the particle size of the WC particles. In the observed image, the particle size of more than 10 (preferably more than 50, more preferably more than 100) randomly selected WC particles is measured, and the arithmetic mean thereof is taken as the average particle size of the WC particles. During observation, the cut surface is preferably cross-sectioned by a cross section polisher (Cross section Polisher; CP) or a focused ion beam (Focused Ion Beam; FIB).

[0125] 《Laminating》

[0126] The coating 20 is provided on the substrate 10. The coating 20 may be provided on a portion of the surface of the substrate 10 or on the entire surface. The coating 20 is provided on at least a portion of the surface of the substrate 10 corresponding to the cutting edge. In the present disclosure, the portion of the surface of the substrate 10 corresponding to the cutting edge refers to an area on the surface of the substrate 10 that is within 0.5 mm or within 2 mm from the edge line of the blade tip. As long as the effect of the present disclosure is not impaired, even if the coating is not formed on at least a portion of the portion corresponding to the cutting edge, it does not deviate from the scope of the present disclosure.

[0127] The coating 20 includes a first layer 21 and a second layer 22. The second layer 22 may be disposed just above the substrate 10. The first layer 21 may be the outermost layer of the coating 20. The coating 20 may be composed of a second layer 22 disposed just above the substrate 10 and a first layer 21 disposed just above the second layer 22. As long as the effects of the present disclosure are not impaired, the coating 20 may also include other layers while including the first layer 21 and the second layer 22. For example, the coating 20 may include one or both of a base layer disposed between the substrate 10 and the second layer 22, and a surface layer disposed at the outermost surface of the coating 20. The base layer may include at least one layer selected from the group consisting of a TiCN layer, a TiN layer, and a TiCNO layer. The surface layer may include at least one layer selected from the group consisting of a TiC layer, a TiN layer, and a TiCN layer.

[0128] The layered structure of the coating 20 does not need to be the same throughout the entire coating 20 , and the layered structure may be different in some areas.

[0129] The thickness of the coating 20 can be greater than 1.5 μm and less than 30 μm. By making the thickness of the coating 20 greater than 1.5 μm, the wear resistance is improved. By making the thickness of the coating 20 less than 30 μm, the defect resistance is improved. The thickness of the coating 20 can be greater than 2.0 μm and less than 25 μm, or greater than 3.0 μm and less than 20 μm. Here, the thickness of the coating refers to the sum of the thicknesses of the various layers constituting the coating. Examples of "layers constituting the coating" include a first layer, a second layer, a base layer, a surface layer, and the like.

[0130] The thickness of each layer constituting the coating is measured as follows: a thin slice sample (hereinafter also referred to as a "cross-section sample") having a cross section parallel to the normal direction of the surface of the cutting tool is obtained, and the cross-section sample is observed using a scanning transmission electron microscope (STEM). As a scanning transmission electron microscope, for example, JEM-2100F (trade name) manufactured by JEOL Ltd. is cited. The observation magnification of the cross-section sample is set to 5000 to 10000 times, and the thickness of five locations of each layer is measured, and the arithmetic mean thereof is taken as the "thickness of each layer".

[0131] It was confirmed that, as long as the measurement is performed using the same cutting tool, there is no variation in the measurement results even if the measurement location is arbitrarily selected.

[0132] The First Layer

[0133] The first layer 21 is composed of a multilayer structure in which first unit layers 1 and second unit layers 2 are alternately stacked. As long as the average thickness of each of the first unit layer 1 and the second unit layer 2 is greater than 2 nm and less than 50 nm, the number of stacking layers is not particularly limited. The number of stacking layers represents the number of each of the first unit layer 1 and the second unit layer 2 contained in the first layer 21. The number of stacking layers can be greater than 10 and less than 5000, or greater than 200 and less than 5000, or greater than 400 and less than 2000, or greater than 500 and less than 1000. In the first layer 21, the layer closest to the substrate 10 can be the first unit layer 1 or the second unit layer 2. In addition, in the first layer 21, the layer farthest from the substrate 10 can be the first unit layer 1 or the second unit layer 2.

[0134] The average thickness of the first layer can be set to be greater than 1.0 μm and less than 20 μm. By making the average thickness of the first layer greater than 1.0 μm, wear resistance is improved. By making the average thickness of the first layer less than 20 μm, defect resistance is improved. The lower limit of the average thickness of the first layer can be greater than 1.0 μm, or greater than 2.0 μm, or greater than 3.0 μm. The upper limit of the average thickness of the first layer can be less than 20 μm, or less than 18 μm, or less than 16 μm, or less than 12 μm. The average thickness of the first layer can be greater than 1.0 μm and less than 20 μm, or greater than 2.0 μm and less than 16 μm, or greater than 3.0 μm and less than 12 μm.

[0135] 《Average thickness of the first unit layer and the second unit layer》

[0136] The average thickness of the first unit layer 1 is greater than 2nm and less than 50nm, and the average thickness of the second unit layer 2 is greater than 2nm and less than 50nm. In the first layer, by alternately stacking such thin layers, the progress of cracks can be suppressed. If the average thickness of one or both of the first unit layer 1 and the second unit layer 2 is less than 2nm, the composition of the first unit layer 1 and the second unit layer 2 is mixed, and the effect of suppressing the progress of cracks may be reduced. If the average thickness of one or both of the first unit layer 1 and the second unit layer 2 exceeds 50nm, the effect of suppressing interlayer delamination may be reduced. The average thickness of the first unit layer and the average thickness of the second unit layer may be the same or different.

[0137] The lower limit of the average thickness of the first unit layer is 2 nm or more, 4 nm or more, 6 nm or more, or 8 nm or more. The upper limit of the average thickness of the first unit layer is 50 nm or less, 46 nm or less, 40 nm or less, or 30 nm or less. The average thickness of the first unit layer is 2 nm or more and 50 nm or less, 4 nm or more and 40 nm or less, or 6 nm or more and 30 nm or less.

[0138] The lower limit of the average thickness of the second unit layer is 2 nm or more, 4 nm or more, 6 nm or more, or 8 nm or more. The upper limit of the average thickness of the second unit layer is 50 nm or less, 46 nm or less, 40 nm or less, or 30 nm or less. The average thickness of the second unit layer is 2 nm or more and 50 nm or less, 4 nm or more and 40 nm or less, or 6 nm or more and 30 nm or less.

[0139] The method for measuring the average thickness of each of the first unit layer and the second unit layer is as follows. A thin slice sample of the cross section of the cutting tool parallel to the normal direction of the surface of the cutting tool (hereinafter also referred to as a "cross section sample") is obtained. The cross section sample is observed using a scanning transmission electron microscope (STEM). As a scanning transmission electron microscope, for example, JEM-2100F (trade name) manufactured by JEOL Ltd. can be cited. The observation magnification of the cross section sample is appropriately adjusted according to the thickness of the first unit layer 1 and the second unit layer 2. For example, the observation magnification can be set to about 1 million times. In a first unit layer, the thickness of five parts is measured. The arithmetic mean of the thickness of the five parts of the first unit layer is calculated, and the arithmetic mean is used as the average thickness of the first unit layer. In a second unit layer, the thickness of five parts is measured.

[0140] For five different first unit layers, the average thickness of the first unit layer is measured according to the above steps. The arithmetic mean of the average thicknesses of the five first unit layers is calculated. In the present disclosure, the arithmetic mean is used as the average thickness of the first unit layer. For five different second unit layers, the average thickness of the second unit layer is measured according to the above steps. The arithmetic mean of the average thicknesses of the five second unit layers is calculated. In the present disclosure, the arithmetic mean is used as the average thickness of the second unit layer. The average thickness of each of the third unit layer and the fourth unit layer described later is also measured by the same method as above.

[0141] It was confirmed that, as long as the measurement is performed using the same cutting tool, there is no variation in the measurement results even if the measurement location is arbitrarily selected.

[0142] 《Composition of the first unit layer and the second unit layer》

[0143] In the cutting tool of the present disclosure, the first unit layer is composed of Ti a Al 1-a-b B b N, wherein 0.30≤a≤0.50, 0<b≤0.10 are satisfied, and the second unit layer is composed of Ti c Al 1-c N, wherein 0.70≤c≤1.00 is satisfied. As long as the effects of the present disclosure are not impaired, the first unit layer may contain Ti a Al 1-a-b B b N and impurities. The first unit layer can be made of Ti a Al 1-a-b B b N and impurities. As long as the effect of the present disclosure is not impaired, the second unit layer may contain Ti c Al 1-c N and impurities. The second unit layer can be made of Ti c Al 1-c N and impurities. Examples of the impurities include carbon (C) and oxygen (O).

[0144] In the first unit layer, the lower limit of a is 0.30 or more, and may be 0.36 or more, 0.37 or more, or 0.39 or more. The upper limit of a is 0.50 or less, and may be 0.48 or less, or 0.45 or less. a may be 0.36≤a≤0.48, or 0.37≤a≤0.45.

[0145] In the first unit layer, the lower limit of b is greater than 0, and may be greater than 0.01, greater than 0.02, or greater than 0.05. The upper limit of b is less than 0.10, less than 0.08, or less than 0.07. b may be 0.01≤b≤0.08, or 0.02≤b≤0.07.

[0146] In the second unit layer, the lower limit of c is 0.70 or more, and may be 0.75 or more, 0.80 or more, or 0.87 or more. The upper limit of c is 1.00 or less, and may be 0.95 or less, or 0.92 or less. c may be 0.75≤d≤0.95, or 0.80≤d≤0.92.

[0147] Ti of the first unit layer a Al 1-a-b B b a, b in N and Ti in the second unit layer c Al 1-c The c in N is determined by measuring the composition of each layer using energy dispersive X-ray spectrometry (EDX). The composition analysis uses EDX (TEM-DEX) attached to a transmission electron microscope (TEM). Examples of the EDX apparatus include JED-2300 (trademark) manufactured by JEOL Ltd.

[0148] The above composition analysis is performed according to the following steps. A thin slice sample (hereinafter also referred to as a "cross-section sample") having a cross section parallel to the normal direction of the surface of the cutting tool is obtained. While observing the cross-section sample with a TEM, EDX analysis is performed on five points arbitrarily selected in a first unit layer or a second unit layer. The first unit layer and the second unit layer can be distinguished by the difference in contrast. Here, the "randomly selected five points" are selected from different grains. The composition of each of the first unit layer and the second unit layer is determined by taking the arithmetic average of the composition ratios of each element obtained in the measurement of the five points.

[0149] For five different first unit layers, the composition of the first unit layer is determined according to the above steps. In the present disclosure, the average composition of the five first unit layers is taken as the composition of the first unit layer, and a and b are determined based on this. For five different second unit layers, the composition of the second unit layer is determined according to the above steps. In the present disclosure, the average composition of the five second unit layers is taken as the composition of the second unit layer, and c is determined based on this. The compositions of the third unit layer and the fourth unit layer described later, and Ti of the third unit layerd Al 1-d-e B e d and e in N, Ti in the fourth unit layer f Al 1-f- g B g f and g in N are also measured by the same method as above.

[0150] It was confirmed that as long as the measurement is performed using the same cutting tool, there is no variation in the measurement results even if the measurement points are arbitrarily selected.

[0151] The composition of the first layer

[0152] In the first layer, the percentage (T2 / T1)×100 (hereinafter, also referred to as "percentage (T2 / T1)×100") of the number of titanium atoms T2 relative to the total number of titanium and aluminum atoms T1 is 60% or more. As a result, the first layer can have excellent crater wear resistance. From the viewpoint of improving crater wear resistance, the lower limit of the percentage (T2 / T1)×100 is 60% or more, and may be 60.0% or more, 62.2% or more, 62.5% or more, 63% or more, 63.5% or more, or 66% or more. From the viewpoint of improving oxidation resistance, the upper limit of the percentage (T2 / T1)×100 may be 80% or less, 77% or less, 76.9% or less, or 75% or less. The percentage (T2 / T1)×100 may be 60% or more and 80% or less, 63% or more and 77% or less, or 66% or more and 75% or less.

[0153] The percentage (T2 / T1)×100 in the first layer is measured by TEM-EDX. An example of an EDX apparatus is JED-2300 (trade name) manufactured by JEOL Ltd. The percentage (T2 / T1)×100 is measured by the following procedure.

[0154] A thin slice sample (hereinafter also referred to as a "cross-section sample") having a cross section parallel to the normal direction of the surface of the cutting tool is obtained. While observing the cross-section sample with a TEM, EDX analysis is performed in five randomly selected fields of view within the first layer to measure the percentage (T2 / T1)×100 of the number of titanium atoms T2 relative to the total number of titanium and aluminum atoms T1. Here, the "randomly selected five fields of view" are set not to overlap each other. The range of one field of view is 200×200nm. In the present disclosure, the arithmetic average of the percentages (T2 / T1)×100 obtained in the measurement of the five fields of view is set as the percentage (T2 / T1)×100 in the first layer.

[0155] It was confirmed that as long as the measurement is performed using the same cutting tool, there is no variation in the measurement results even if the measurement points are arbitrarily selected.

[0156] Nanoindentation hardness of the first layer

[0157] The nanoindentation hardness of the first layer at 25°C may be 30 GPa or more. Thus, the wear resistance of the cutting tool is improved. The lower limit of the nanoindentation hardness may be 32 GPa or more, or 34 GPa or more. There is no particular limit to the upper limit of the nanoindentation hardness H. From the manufacturing point of view, it may be 60 GPa or less, 40 GPa or less, or 36 GPa or less. The nanoindentation hardness H may be 30 GPa or more and 60 GPa or more, 32 GPa or more and 60 GPa or less, or 34 GPa or more and 60 GPa or less.

[0158] The nanoindentation hardness of the first layer at 25°C is measured by nanoindentation method according to the standard procedure specified in "ISO 14577-1:2015Metallic materials-Instrumented indentation test for hardness and materials parameters-". The measuring equipment uses "ENT-1100a" manufactured by Elionix. The indentation load of the indenter is set to 1g. In a cross section parallel to the normal direction of the surface of the cutting tool, the indenter is pressed into the first layer in the vertical direction of the cross section (i.e., the direction parallel to the surface of the cutting tool).

[0159] The above measurement was performed at five locations on one measurement sample. The average value of the nanoindentation hardness at the five locations was taken as the nanoindentation hardness of the first layer. In addition, data that were considered abnormal at first glance were excluded.

[0160] It was confirmed that as long as the measurement is performed using the same cutting tool, there is no variation in the measurement results even if the measurement points are arbitrarily selected.

[0161] 《The diameter of the largest inscribed circle of the grains in the first layer》

[0162] The first layer is composed of a plurality of crystal grains, and the diameter of the maximum inscribed circle of the crystal grains can be greater than 5 nm and less than 500 nm. Thus, the crater wear resistance of the cutting tool is improved. The first layer of the present disclosure can include a plurality of crystal grains and a region (a region with random atomic arrangement) that does not constitute a crystal grain within the range that does not impair the effect of the present disclosure.

[0163] From the viewpoint of improving wear resistance and defect resistance, the upper limit of the diameter of the maximum inscribed circle of the above-mentioned grains may be 500nm or less, 450nm or less, or 400nm or less. From the viewpoint of suppressing the reduction in film hardness caused by excessive grain refinement, the lower limit of the diameter of the maximum inscribed circle of the grains may be 5nm or more, 7nm or more, or 10nm or more. The diameter of the maximum inscribed circle of the grains may be 5nm or more and 500nm or less, 7nm or more and 450nm or less, or 10nm or more and 400nm or less.

[0164] The method for measuring the diameter of the maximum inscribed circle of the above-mentioned grain is as follows. A thin slice sample (thickness: about 10 to 100 nm, hereinafter also referred to as "cross-section sample") of the cross section of the cutting tool parallel to the normal direction of the surface of the cutting tool is obtained. The cross-section sample is observed using a transmission electron microscope (TEM) to obtain a bright field image. The observation magnification is set to 1 million times to 5 million times. Figure 4 As shown, the bright field image is acquired in a manner including region A, region A being a region sandwiched between line L2 and line L3, line L2 being a line at a distance of 0.2 μm from line L1 indicating the center in the average thickness direction of the first layer toward the substrate side, and line L3 being a line at a distance of 0.2 μm from the line L1 toward the surface side of the coating. In region A, a rectangular measurement field of 150 nm×150 nm is arbitrarily set.

[0165] In the above measurement field, the area where the atomic arrangement is less than ±0.5° is determined and defined as the crystal grain. Figure 5 A method for determining a region where the atomic arrangement is ±0.5° or less and a crystal grain will be described.

[0166] Figure 5 FIG. 1 is a schematic diagram showing an example of a bright field image of the above-mentioned measurement field. Figure 5 In the diagram, atoms are represented by black dots with reference numeral 50. Figure 5 In the bright field image, atoms 50 arranged regularly are connected by the line segments with the shortest distance between atoms. Figure 5 In FIG. 5 , the line segments are represented by L10 to L14, L20 to L22, and L30 to L34. A region where the angles between the line segments are ±0.5° or less (ie, -0.5° or more and 0.5° or less) is defined as a crystal grain.

[0167] exist Figure 5, the angles between line segments L10 to L14 are less than ±0.5°, and the region including these line segments is equivalent to the grain 24a. The angles between line segments L20 to L22 are less than ±0.5°, and the region including these line segments is equivalent to the grain 24b. The angles between line segments L30 to L34 are less than ±0.5°, and the region including these line segments is equivalent to the grain 24c.

[0168] The diameter of the maximum inscribed circle of each crystal grain in the measurement field is obtained. The diameter of the maximum inscribed circle refers to the diameter of the largest inscribed circle that can be drawn inside the crystal grain and contacts at least a part of the outer edge of the crystal grain.

[0169] exist Figure 5 In the example, the diameter of the largest inscribed circle 25a of the crystal grain 24a is D1. The diameter of the largest inscribed circle 25b of the crystal grain 24b is D2. The diameter of the largest inscribed circle 25c of the crystal grain 24c is D3. When D1, D2, and D3 are all less than 50 nm, it is confirmed that Figure 5 The first layer shown is composed of a plurality of crystal grains, and the diameter of the largest inscribed circle of the crystal grains is 50 nm or less.

[0170] It was confirmed that, as long as the measurement is performed using the same cutting tool, there is no variation in the measurement result of the diameter of the largest inscribed circle of the crystal grain even if the measurement field of view is arbitrarily set.

[0171] exist Figure 5 In the image, there is space between grains 24a, 24b, and 24c, but there are actually grains in the space. The thickness of the cross-section sample used for TEM is about 10 to 100 nm, so the information in the depth direction is also reflected in the bright field image. In the area where multiple grains overlap in the thickness direction of the sample, a regular atomic arrangement cannot be confirmed in the bright field image. Therefore, the area where multiple grains overlap is not identified as a grain in the above-mentioned determination method.

[0172] 《Positional Relationship between Grains and the First and Second Unit Layers》

[0173] use Figure 6 The positional relationship between the crystal grains, the first unit layer, and the second unit layer will be described. Figure 6 Schematically shows a cross section of the first layer along the film thickness direction of Embodiment 1. Figure 6 As shown, the first layer 21 is composed of a multilayer structure in which first unit layers 1 and second unit layers 2 are alternately stacked. Figure 6, a plurality of crystal grains 24 are shown, and the boundaries between the crystal grains 24 are shown as grain boundaries 25. Each crystal grain 24 may be composed of only the first unit layer or the second unit layer. In addition, each crystal grain 24 may exist across one or more first unit layers and one or more second unit layers. That is, each crystal grain 24 may have a layered structure in which the first unit layer and the second unit layer are alternately stacked.

[0174] The Second Layer

[0175] The second layer 22 is composed of a multilayer structure in which the third unit layer 3 and the fourth unit layer 4 are alternately stacked. As long as the average thickness of each of the third unit layer 3 and the fourth unit layer 4 is 2 nm or more and 50 nm or less, the number of stacking layers is not particularly limited. The number of stacking layers represents the number of each of the third unit layer 3 and the fourth unit layer 4 contained in the second layer 22. The number of stacking layers may be 10 or more and 5000 or less, 200 or more and 5000 or less, 400 or more and 2000 or less, or 500 or more and 1000 or less. In the second layer 22, the layer closest to the substrate 10 may be the third unit layer 3 or the fourth unit layer 4. In addition, in the second layer 22, the layer farthest from the substrate 10 may be the third unit layer 3 or the fourth unit layer 4.

[0176] The average thickness of the second layer can be set to be greater than 0.5 μm and less than 10 μm. By making the average thickness of the second layer greater than 0.5 μm, wear resistance is improved. By making the average thickness of the second layer less than 10 μm, defect resistance is improved. The lower limit of the average thickness of the second layer can be greater than 1.0 μm, or greater than 2.0 μm, or greater than 3.0 μm. The upper limit of the average thickness of the second layer can be less than 10 μm, or less than 9 μm, or less than 8 μm, or less than 7 μm. The average thickness of the second layer can be greater than 1.0 μm and less than 9 μm, or greater than 2.0 μm and less than 8 μm, or greater than 3.0 μm and less than 7 μm.

[0177] 《Average thickness of the third unit layer and the fourth unit layer》

[0178] The average thickness of the third unit layer 3 is greater than 2nm and less than 100nm, and the average thickness of the fourth unit layer 4 is greater than 2nm and less than 100nm. In the second layer, by alternately stacking such thin layers, the progress of cracks can be suppressed. If the average thickness of one or both of the third unit layer 3 and the fourth unit layer 4 is less than 2nm, the composition of the third unit layer 3 and the fourth unit layer 4 is mixed, and the effect of suppressing the progress of cracks may be reduced. If the average thickness of one or both of the third unit layer 3 and the fourth unit layer 4 exceeds 100nm, the effect of suppressing interlayer delamination may be reduced. The average thickness of the third unit layer and the average thickness of the fourth unit layer may be the same or different.

[0179] The lower limit of the average thickness of the third unit layer is 2 nm or more, 5 nm or more, 10 nm or more, 15 nm or more, or 20 nm or more. The upper limit of the average thickness of the third unit layer is 100 nm or less, 80 nm or less, 75 nm or less, 65 nm or less, or 64 nm or less. The average thickness of the third unit layer is 2 nm or more and 100 nm or less, 5 nm or more and 75 nm or less, or 10 nm or more and 65 nm or less.

[0180] The lower limit of the average thickness of the fourth unit layer is 2 nm or more, 5 nm or more, 10 nm or more, 15 nm or more, or 20 nm or more. The upper limit of the average thickness of the fourth unit layer is 100 nm or less, 80 nm or less, 75 nm or less, 65 nm or less, 52 nm or less, or 50 nm or less. The average thickness of the fourth unit layer is 2 nm or more and 100 nm or less, 5 nm or more and 75 nm or less, or 10 nm or more and 50 nm or less.

[0181] The average thickness of each of the third unit layer and the fourth unit layer was measured by the same method as the method for measuring the average thickness of each of the first unit layer and the second unit layer. It was confirmed that as long as the measurement was performed using the same cutting tool, there was no deviation in the measurement results even if the measurement site was arbitrarily selected.

[0182] 《Composition of the third unit layer and the fourth unit layer》

[0183] In the cutting tool of the present disclosure, the third unit layer is composed of Ti d Al 1-d-e B e N, wherein 0.25≤d<0.45, 0<e≤0.10 are satisfied, and the fourth unit layer is composed of Ti f Al 1-f-g Bg N, wherein 0.35≤f<0.55, 0<g≤0.10, 0.05≤fd≤0.2 are satisfied. As long as the effects of the present disclosure are not impaired, the third unit layer may contain Ti d Al 1-d-e B e N and impurities. The third unit layer can be made of Ti d Al 1-d-e B e N and impurities. As long as the effects of the present disclosure are not impaired, the fourth unit layer may contain Ti f Al 1-f-g B g N and impurities. The fourth unit layer can be made of Ti f Al 1-f-g B g N and impurities. Examples of the impurities include carbon (C) and oxygen (O).

[0184] In the third unit layer, the lower limit of d is 0.25 or more, and may be 0.30 or more, 0.31 or more, 0.32 or more, 0.33 or more, or 0.34 or more. The upper limit of d is less than 0.45, and may be 0.40 or less, 0.37 or less, or 0.35 or less. d may be 0.30≤d≤0.40, or 0.31≤d≤0.37.

[0185] In the third unit layer, the lower limit of e is greater than 0, and may be greater than 0.01, greater than 0.02, greater than 0.04, or greater than 0.05. The upper limit of e is less than 0.10, less than 0.08, less than 0.07, or less than 0.06. e may be 0.01≤e≤0.08, or 0.02≤e≤0.07.

[0186] In the fourth unit layer, the lower limit of f is 0.35 or more, and may be 0.40 or more, 0.41 or more, 0.42 or more, 0.43 or more, or 0.45 or more. The upper limit of f is less than 0.55, and may be 0.50 or less. c may be 0.40≤f<0.55, or 0.45≤f≤0.50.

[0187] In the fourth unit layer, the lower limit of g is greater than 0, and may be greater than 0.01, greater than 0.02, or greater than 0.04. The upper limit of g is less than 0.10, less than 0.08, or less than 0.06. c may be 0.01≤f≤0.10, or 0.02≤f≤0.06.

[0188] In the second layer, the lower limit of fd is 0.05 or more, and may be 0.08 or more, 0.10 or more, or 0.11 or more. The upper limit of fd is 0.20 or less, and may be 0.18 or less. fd may be 0.08≤fd≤0.18, or 0.10≤fd≤0.18.

[0189] Ti of the third unit layer d Al 1-d-e B e d and e in N, Ti in the fourth unit layer f Al 1-f-g B g f and g in N are connected to Ti in the first unit layer a Al 1-a-b B b a, b in N and Ti in the second unit layer c Al 1-c The c in N was measured in the same manner. It was confirmed that, as long as the measurement was performed using the same cutting tool, there was no variation in the measurement results even if the measurement site was arbitrarily selected.

[0190] 《X-ray diffraction analysis in the second layer》

[0191] In the X-ray diffraction spectrum of the second layer, the ratio I(200) / I(002) of the peak intensity I(200) from the (200) plane to the peak intensity I(002) from the (002) plane is 2 or more, and the half-value width of the peak from the (002) plane is 2 degrees or more. As a result, the hardness and toughness of the second layer are improved, and excellent wear resistance and defect resistance can be obtained. "Peak intensity I(002) from the (002) plane" refers to the diffraction intensity (peak height) at the highest peak in the X-ray diffraction peak from the (002) plane of the hexagonal crystal. "Peak intensity I(200) from the (200) plane" refers to the diffraction intensity (peak height) at the highest peak in the X-ray diffraction peak from the (200) plane of the cubic crystal. In the X-ray diffraction spectrum of the second layer, in the presence of a peak from the (002) plane of the hexagonal crystal, it is confirmed that the second layer contains a hexagonal crystal structure. In the X-ray diffraction spectrum of the second layer, when there is a peak from the (200) plane of the cubic crystal, it is confirmed that the second layer includes a cubic crystal structure. The ratio I(200) / I(002) being 2 or more means that a mixed crystal of cubic and hexagonal crystals is formed in the second layer.

[0192] The conditions for X-ray diffraction analysis when measuring the peak intensity I(002) and the peak intensity I(200) are as follows.

[0193] Scanning axis: 2θ-θ

[0194] X-ray source: Cu-Kα ray

[0195] Detector: 0-dimensional detector (scintillation counter)

[0196] Tube voltage: 45kV

[0197] Tube current: 40mA

[0198] Incident optical system: using a reflector

[0199] Light receiving optical system: Utilizes analyzer crystal (PW3098 / 27)

[0200] Step length: 0.03°

[0201] Cumulative time: 2 seconds

[0202] Scanning range (2θ): 20°~80°

[0203] At any three locations in the second layer, X-ray diffraction measurement (XRD measurement) based on the θ / 2θ method is performed to obtain the X-ray diffraction intensity of the predetermined crystal plane, and the average value of the X-ray diffraction intensities of the three locations is used as the X-ray diffraction intensity of the predetermined crystal plane. The X-ray diffraction intensity of the (200) plane corresponds to the X-ray diffraction intensity near 2θ=43~44°, and the X-ray diffraction intensity of the (002) plane corresponds to the X-ray diffraction intensity near 2θ=30~40°. As an apparatus used in the X-ray diffraction measurement, for example, "SmartLab" (trade name) manufactured by Rigaku Co., Ltd., "X'pert" (trade name) manufactured by PANalytical, etc. can be cited.

[0204] The lower limit of the ratio I(200) / I(002) is 2 or more, and may be 2.0 or more, 2.2 or more, or 2.3 or more. The upper limit of the ratio I(200) / I(002) may be, for example, 10 or less, less than 10, 5 or less, or 3 or less. The ratio I(200) / I(002) may be 2 or more and 10 or less, or 2 or more and 5 or less.

[0205] The half-value width of the peak from the (002) face is 2 degrees or more, which means that the hexagonal crystals are finely dispersed in the second layer, so that the hardness and toughness are improved. The lower limit of the half-value width of the peak from the (002) face is 2 degrees or more, and it can also be 2.0 degrees or more, or it can be 2.2 degrees or more. The upper limit of the half-value width of the peak from the (002) face can be 4 degrees or less, or it can be 3 degrees or less. The lower limit of the half-value width of the peak from the (002) face can be 2 degrees or more, or it can be 2.2 degrees or more, or it can be 2.4 degrees or more. The half-value width of the peak from the (002) face can be 2 degrees or more and 4 degrees or less, or it can be 2 degrees or more and 3 degrees or less.

[0206] [Embodiment 2: Method for manufacturing cutting tool]

[0207] In Embodiment 2, a method for manufacturing the cutting tool of Embodiment 1 will be described. The manufacturing method of Embodiment 2 may include a step of preparing a substrate and a step of forming a coating on the substrate. The details of each step will be described below.

[0208] 《Process of preparing base material》

[0209] In the step of preparing a substrate, a substrate 10 is prepared. As the substrate 10, the substrate described in Embodiment 1 can be used.

[0210] 《Process of forming a coating》

[0211] In the step of forming the coating, the coating 20 is formed on the substrate 10. In the second embodiment, the coating 20 can be formed by a physical vapor deposition (PVD) method. Specific examples of the PVD method include an arc ion plating (AIP) method, a balanced magnetron sputtering (BMS) method, and an unbalanced magnetron sputtering (UBMS) method. In the second embodiment, arc ion plating is preferably used.

[0212] In the AIP method, an arc discharge is generated with a target as a cathode. As a result, the target is evaporated and ionized. Then, the ions are deposited on the surface of the substrate 10 to which a negative bias voltage is applied. The AIP method is excellent in the ionization rate of the target.

[0213] use Figure 2 as well as Figure 3 The film forming apparatus used in the AIP method is described below. Figure 2As shown, the film forming apparatus 200 includes a chamber 201. The chamber 201 is provided with a gas inlet 202 for introducing a raw material gas into the chamber 201, and a gas exhaust port 203 for exhausting the raw material gas from the chamber 201 to the outside. The gas exhaust port 203 is connected to a vacuum pump (not shown). The pressure in the chamber 201 is adjusted by the amount of gas introduced and exhausted.

[0214] A rotating table 204 is disposed in the chamber 201. A substrate holder 205 for holding the substrate 10 is mounted on the rotating table 204. The substrate holder 205 is connected to the negative electrode of a bias power supply 206. The positive electrode of the bias power supply 206 is grounded.

[0215] like Figure 3 As shown, a plurality of targets 211, 212, 213, and 214 are installed on the side wall of the chamber 201. Figure 2 As shown, each target 211, target 212 is connected to the negative pole of the DC power supply 221, DC power supply 222. The DC power supply 221, DC power supply 222 is a variable power supply, and its positive pole is grounded. Figure 2 Although not shown in the figure, the same is true for the target 213 and the target 214. The specific operation will be described below.

[0216] The substrate 10 is held on the substrate holder 205. The pressure in the chamber 201 is adjusted to 1.0×10 - 4 Pa. While the turntable 204 is rotated, the temperature of the substrate 10 is adjusted to 500° C. using a heater (not shown) included in the film forming apparatus 200 .

[0217] Ar gas was introduced from the gas inlet 202 to adjust the pressure in the chamber 201 to 3.0 Pa. While maintaining this pressure, the voltage of the bias power supply 206 was gradually changed and finally adjusted to -1000 V. Then, the surface of the substrate 10 was cleaned by ion bombardment treatment with Ar ions.

[0218] Next, when the coating film includes an underlayer, the underlayer is formed on the surface of the substrate 10. For example, a TiCN layer, a TiN layer, or a TiCNO layer is formed on the surface of the substrate 10.

[0219] Next, a second layer is formed on the surface of the substrate 10 or the surface of the base layer. The composition of each target material is selected to obtain the composition of the third unit layer and the fourth unit layer. Each target material is set at a predetermined position, and nitrogen gas is introduced from the gas inlet 202. The second layer is formed while the rotating table 204 is rotated. When forming the second layer, the substrate is maintained at a temperature of 400 to 800°C, the reaction gas pressure is maintained at 1 to 10Pa (the partial pressure of nitrogen is 5 to 10Pa), the voltage of the bias power supply is gradually changed in the range of 30 to 200V (DC power supply), and an arc current of 80 to 200A is alternately supplied to the evaporation source for forming the third unit layer and the evaporation source for forming the fourth unit layer. As a result, metal ions are generated from the evaporation source for forming the third unit layer and the evaporation source for forming the fourth unit layer, and the third unit layer is formed when the above-mentioned substrate and the evaporation source for forming the third unit layer are opposite, and the fourth unit layer is formed when the above-mentioned substrate and the evaporation source for forming the fourth unit layer are opposite. In addition, by performing film formation while changing the voltage of the bias power supply as described above, it is possible to achieve both high hardness of the second layer and quality of the blade tip. The supply of arc current is stopped after a predetermined time has passed. When forming the second layer, the thickness of each of the third unit layer and the fourth unit layer is adjusted by adjusting the rotation speed of the substrate. In addition, by adjusting the film formation time, the thickness of the second layer is adjusted to a predetermined range. On the basis of the portion involved in the cutting process (for example, the front cutting face near the cutting edge), the second layer can also be formed on the surface of the above-mentioned substrate other than the portion involved in the cutting process.

[0220] In one aspect of the present embodiment, the substrate may be maintained at a temperature of 500 to 600°C, the reaction gas pressure may be maintained at 5 to 10 Pa (the partial pressure of nitrogen is 5 to 8 Pa), the voltage of the bias power supply may be gradually changed within the range of 30 to 200 V (DC power supply), and an arc current of 80 to 120 A may be alternately supplied to the evaporation source for forming the third unit layer and the evaporation source for forming the fourth unit layer. Thus, a mixed crystal structure of cubic crystals and hexagonal crystals may be formed in the second layer. By forming such a mixed crystal structure, the coarsening of the grains of the cubic crystals and the hexagonal crystals may be suppressed, thereby improving the toughness and heat resistance of the second layer.

[0221] Next, the first layer is formed on the second layer. The composition of each target is selected to obtain the composition of the first unit layer and the second unit layer. Each target is set at a predetermined position, and nitrogen gas is introduced from the gas inlet 202, and the first layer is formed while rotating the rotating table 204. The formation conditions of the first layer are as follows.

[0222] <Formation conditions of the first layer>

[0223] Substrate temperature: 400~800℃

[0224] Bias voltage: -400~-20V

[0225] Arc current: 80~200A

[0226] Reaction gas pressure: 2~10Pa

[0227] The substrate temperature, reaction gas pressure, bias voltage, and arc current are set to be constant values ​​within the above ranges, or the values ​​are continuously changed within the above ranges.

[0228] The multilayer structure in which the first unit layers and the second unit layers are alternately stacked can be formed by appropriately combining the following methods (A) to (D).

[0229] (A) In the AIP method, a plurality of targets (sintered alloys) having different compositions are used.

[0230] (B) In the AIP method, during film formation, the bias voltage applied to the substrate 10 is changed within the bias voltage range described in the above-mentioned formation conditions of the first layer.

[0231] (C) In the AIP method, the gas flow rate is changed.

[0232] (D) In ​​the AIP method, the substrate 10 is rotated and the rotation cycle is controlled.

[0233] Next, when the coating film includes a surface layer, the surface layer is formed on the surface of the first layer, for example.

[0234] As described above, it is possible to manufacture the cutting tool 100 including the substrate 10 and the coating 20 provided on the substrate 10 .

[0235] Example

[0236] The present embodiment will be described in more detail by way of examples, but the present embodiment is not limited to these examples.

[0237] [Example 1]

[0238] <Manufacturing of cutting tools>

[0239] Cutting tools were produced as follows, and tool life was evaluated.

[0240] As a substrate, a cutting insert made of cemented carbide (model: CNMG120408 (manufactured by Sumitomo Electric Hardmetal Co., Ltd.) was prepared. The cemented carbide contained WC particles (90% by mass) and Co (10% by mass). The average particle size of the WC particles was 1 to 2 μm.

[0241] On the above substrate, using Figure 2 as well as Figure 3The coating is formed by using a film forming apparatus having the structure shown in the figure. First, the surface of the substrate is cleaned by ion bombarding the substrate with Ar ions. The specific conditions of the ion bombardment treatment are as described in the second embodiment.

[0242] Next, the target material was placed at a predetermined position of the film forming apparatus. The composition of each target material was adjusted so as to obtain the compositions of the first and second cell layers listed in Table 1 and the compositions of the third and fourth cell layers listed in Table 2.

[0243] A second layer is formed on the substrate. Specifically, nitrogen gas is introduced from the gas inlet, and the third unit layer and the fourth unit layer are alternately formed while the turntable is rotated, thereby forming the second layer. The substrate is maintained at a temperature of 550°C, the reaction gas pressure is maintained at 8Pa (partial pressure of nitrogen: 8Pa), and the voltage of the bias power supply is gradually changed within the range of 35 to 180V, while an arc current of 90A is alternately supplied to the evaporation source for forming the third unit layer and the evaporation source for forming the fourth unit layer. The thickness of each of the third unit layer and the fourth unit layer and the number of layers are adjusted by the rotation speed of the substrate.

[0244] Next, the first layer is formed on the second layer. Specifically, nitrogen gas is introduced from the gas inlet, and the first unit layer and the second unit layer are alternately formed while the turntable is rotated, thereby forming the first layer on the second layer. The formation conditions of the first layer of each sample are set to a substrate temperature of 400 to 800°C, a bias voltage of -400 to -20V, an arc current of 80 to 200A, and a reaction gas pressure of 2 to 10Pa. The substrate temperature, reaction gas pressure, bias voltage and arc current are set to be constant values ​​within the above range, or the values ​​are continuously changed within the above range. The thickness of each of the first unit layer and the second unit layer and the number of layers are adjusted by the rotation speed of the substrate. Through the above process, the cutting tool of each sample is obtained.

[0245] <Evaluation>

[0246] 《Composition of coating》

[0247] For the coating of each sample, the composition of the first unit layer, the second unit layer, the third unit layer and the fourth unit layer, the average thickness, the number of stacking layers, the average thickness of the first layer and the second layer, the percentage of the number of titanium atoms relative to the total number of titanium and aluminum atoms in the first layer (expressed as "(T2 / T1)×100" in Table 1), the nanoindentation hardness of the first layer (expressed as "Hardness" in Table 1), the ratio I(200) / I(002) of the second layer, and the half-value width of the peak from the (002) plane (expressed as "(002) peak half-value width" in Table 2) were measured. The measurement method of each item is as described in Implementation Example 1. The results are shown in Tables 1 and 2. The expression "1" in "Number of stacking layers" in Table 1 indicates that only one first unit layer or second unit layer is formed. The expression "-" in Table 1 indicates that the corresponding layer is not formed.

[0248] Table 1

[0249]

[0250] Table 2

[0251]

[0252] 《Cutting Test》

[0253] The cutting tool of each sample was used for turning under the following conditions, and the cutting distance until the width of the defect measured from the back face reached 0.5 mm or more was measured. The longer the cutting distance, the better the crater wear resistance and defect resistance, and the longer the tool life. The results are shown in the "Cutting Distance" column of "Cutting Test" in Table 3.

[0254] (Cutting conditions)

[0255] Cutting parts: SUS316 round parts

[0256] Cutting speed: 200m / min

[0257] Feed rate: 0.2mm / re v

[0258] Cutting amount: 1.5mm

[0259] Wet

[0260] The above-mentioned cutting conditions correspond to the turning process (high-speed machining) of stainless steel.

[0261] Table 3

[0262]

[0263] <Evaluation>

[0264] Samples 1 to 15 correspond to Examples. Samples 21 to 28 correspond to Comparative Examples. It was confirmed that the tool life of Samples 1 to 15 was longer than that of Samples 21 to 28.

[0265] As mentioned above, although the embodiment and the example of this disclosure were described, it is also planned from the beginning that the configurations of each embodiment and the example described above are appropriately combined or variously modified.

[0266] The embodiments and examples disclosed herein are illustrative in all aspects and should not be construed as restrictive. The scope of the present disclosure is indicated by the claims rather than the embodiments and is intended to include all modifications within the scope and meaning equivalent to the claims.

[0267] Description of Reference Numerals

[0268] 1: first unit layer; 2: second unit layer; 3: third unit layer; 4: fourth unit layer; 10: substrate; 20: coating; 21: first layer; 22: second layer; 24, 24a, 24b, 24c: grains; 25: grain boundaries; 50: atoms; 100: cutting tool; 200: film forming device; 201: chamber; 202: gas inlet; 203: gas exhaust port; 204: turntable; 205: substrate holder; 206: bias power supply; 211, 212, 213, 214: targets; 221, 222: DC power supply.

Claims

1. A cutting tool comprising a substrate and a coating provided on the substrate, wherein: The coating comprises a first layer and a second layer, The second layer is disposed closer to the substrate than the first layer. The first layer is composed of a multilayer structure in which first unit layers and second unit layers are alternately stacked. The average thickness of the first unit layer is greater than or equal to 2 nm and less than or equal to 50 nm. The average thickness of the second unit layer is greater than or equal to 2 nm and less than or equal to 50 nm. The first unit layer is made of Ti a Al 1-a-b B b N constitutes, in, Satisfy 0.30≤a≤0.50, 0<b≤0.10, The second unit layer is made of Ti c Al 1-c N constitutes, in, Satisfying 0.70≤c≤1.00, In the first layer, the percentage (T2 / T1)×100 of the number of titanium atoms T2 to the total number of titanium and aluminum atoms T1 is 60% or more, The second layer is composed of a multilayer structure in which third unit layers and fourth unit layers are alternately stacked. The average thickness of the third unit layer is greater than or equal to 2 nm and less than or equal to 100 nm. The average thickness of the fourth unit layer is greater than or equal to 2 nm and less than or equal to 100 nm, The third unit layer is composed of Ti d Al 1-d-e B e N constitutes, The fourth unit layer is composed of Ti f Al 1-f-g B g N constitutes, in, Satisfy 0.25≤d<0.45, 0<e≤0.10、 0.35≤f<0.55、 0<g≤0.10、 0.05≤fd≤0.20, In the X-ray diffraction spectrum of the second layer, the ratio I(200) / I(002) of the peak intensity I(200) from the (200) plane to the peak intensity I(002) from the (002) plane is greater than 2, and the half-value width of the peak from the (002) plane is greater than 2 degrees.

2. The cutting tool according to claim 1, wherein: The nanoindentation hardness of the first layer at 25° C. is 30 GPa or more.

3. The cutting tool according to claim 1 or 2, wherein: The average thickness of the first layer is 1.0 μm or more and 20 μm or less.

4. The cutting tool according to any one of claims 1 to 3, wherein: The average thickness of the second layer is 0.5 μm or more and 10 μm or less.